ANALYSIS OF IMMUNOGYSTOCHEMICAL EXAMINATION OF RESPIRATORY ORGANS IN EXPERIMENTAL BRONCHOECTASIS (World Bulletin of Public Health, 2024)
Immunohistochemical methods for the study of lung tissue in bronchiectatic disease in experimental animal conditions are necessary for a deeper understanding of the cellular and molecular mechanisms of chronic respiratory diseases and the development of new approaches to their diagnosis and therapy
Keywords: bronchi; lungs; chronic inflammation